Core/shell CoFe\(_{2}\)O\(_{4}\)/Fe\(_{3}\)O\(_{4}\) nanoparticles: effects of hard/soft magnetic weight fraction on structure, particle size and magnetic properties - Nga, Tran Thi Viet; Hung, Chu Manh; Duong, Truong Tien Hoang (Communications in Physics, 2023)
CoFe\(_{2}\)O\(_{4}\)/Fe\(_{3}\)O\(_{4}\) nanocomposite particles were synthesized by using co-precipitation combined with hydrothermal methods. The phase composition, surface morphology and magnetic properties of the nanocomposites were investigated using X- ray diffraction, scanning electron microscopy and vibrating sample magnetometer. Findings show that the samples comprise two phases, and Fe\(_{3}\)O\(_{4}\) particles are coated on the surface of CoFe\(_{2}\)O\(_{4}\) particles. The average particle size of CoFe\(_{2}\)O\(_{4}\) was ditrisbuted in the range of 50 -- 100 nm. While the particle of Fe\(_{3}\)O\(_{4}\) displayed a spherical shape and particle size distributed from 10 -- 20 nm. The MS of CoFe\(_{2}\)O\(_{4}\)@Fe\(_{3}\)O\(_{4}\) core–shell particles increase with the decrease in the mass ratio of hard to soft ferrites. The structure, magnetic properties and the degree of exchange coupling between the magnetic phases were investigated.